Bankowość modemowa jako rodzaj bankowości komputerowej - Solarz, Małgorzata (Modem Banking as a Kind of PC Banking, 2005)
For the last ten years the Polish financial services market has seen a moderate development of modem banking services. The number of e-banking services has been gradually increasing, along with the number of customers using their home PCs to communicate with their bank via phone and modem. In the years 1995-1996 the most, over 21 financial institutions lunched modem banking systems. At the end of February of 2003 this kind of services were offered by over 40 banks. The most dynamic in achieving market share was ING Bank Śląski SA, In that terms, we have to take: BRE Bank SA, Bank Pekao SA and Kredyt Bank SA into account. These systems are very popular due to the wide range of possibility, which their offer their users. On the other hand due to high costs of using these systems, it is mainly offered to big companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 248-260